A review on integrated battery chargers for electric vehicles - Sousa, Tiago José Cunha (2022)
Electric vehicles (EVs) contain two main power electronics systems, namely, the traction system and the battery charging system, which are not used simultaneously since traction occurs when the EV is travelling and battery charging when the EV is parked. By taking advantage of this interchangeability, a single set of power converters that can perform the functions of both traction and battery charging can be assembled, classified in the literature as integrated battery chargers (IBCs). Several IBC topologies have been proposed in the literature, and the aim of this paper is to present a literature review of IBCs for EVs. In order to better organize the information presented in this paper, the analyzed topologies are divided into classical IBCs, IBCs for switched reluctance machines (SRMs), IBCs with galvanic isolation, IBCs based on multiple traction converters and IBCs based on multiphase machines. A comparison between all these IBCs is subsequently presented, based on both requirements and possible functionalities.